The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00054806
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic stability of multiple growth twins in quartz and general geobarothermometric implications

Abstract: Al~tract. The thermoelastic analysis of the possible stable stress-free equilibrium states of polycrystals provides a theoretical way of distinguishing "true" twins from random intergrowths. We analyze in detail a four-fold cyclic twin in quartz, and we show that this gives also the basis for a new technique of geobarothermometry. To obtain the harothermometric function, the simultaneous dependence upon the external pressure and temperature of the lattice-parameter has been estimated; an explicit five-paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…As to how mineralogists interpret "parts", I will analyze two examples of trilling, suggesting three parts, in configurations involving six sections1 opposite sections have the same orientation, so just three orientations are involved. The 90 1 crosses in quartz that Zanzotto [6,7] and I [8] analyzed do allow for some different arrangements of shifts: we did not find observations of these. I shall discuss one of the solutions that qualifies as a cyclic twin, partly to introduce another possible interpretation of the analysis.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…As to how mineralogists interpret "parts", I will analyze two examples of trilling, suggesting three parts, in configurations involving six sections1 opposite sections have the same orientation, so just three orientations are involved. The 90 1 crosses in quartz that Zanzotto [6,7] and I [8] analyzed do allow for some different arrangements of shifts: we did not find observations of these. I shall discuss one of the solutions that qualifies as a cyclic twin, partly to introduce another possible interpretation of the analysis.…”
contrasting
confidence: 62%
“…After going through these examples, it occurred to me that the analyses that Zanzotto [6,7] and I [8] did of the 90 1 crosses in 6-quartz, sometimes called low quartz, might be interpreted in a different way. In terms of the usual orthonormal basis, the lattice vectors are of the form Clearly, e 1 6 e 2 bisects the angle between these, thus forming 45 1 angles with both.…”
Section: Quartz Crosses As Fourlingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Zanzotto [24,25] had done interesting studies of the effects of pressure and temperature on rare quartz crosses involving these, my studies adding a little to his theory. He found that, in general, changes in pressure and/ or temperature induce shear stresses in such configurations unless their values lie on certain curves.…”
Section: Other Twinsmentioning
confidence: 96%
“…Here, (22) 7 requires that, for (9) to be satisfied, ghw T @ ghw p @ 4 and, for simplicity, I will only consider the possibility ghw T @ ghw p @ 4> (25) except where there is a note to the contrary. Then, the work of Pitteri [19] shows that, with U y denoting the rotation with axis y and angle # , either…”
Section: Commonly Observed Twinsmentioning
confidence: 99%